Engineering a Disulfide Bond in the Lid Hinge Region of Rhizopus chinensis Lipase: Increased Thermostability and Altered Acyl Chain Length Specificity - Yu, Xiao-Wei; Tan, Nian-Jiang; Xiao, Rong; Xu, Yan (PLOS ONE, 2012)
The key to enzyme function is the maintenance of an appropriate balance between molecular stability and structural flexibility. The lid domain which is very important for “interfacial activation” is the most flexible part in the lipase structure. In this work, rational design was applied to explore the relationship between lid rigidity and lipase activity by introducing a disulfide bond in the hinge region of the lid, in the hope of improving the thermostability of R. chinensis lipase through stabilization of the lid domain without interfering with its catalytic performance. A disulfide bridge between F95C and F214C was introduced into the lipase from R. chinensis in the hinge region of the lid according to the prediction of the “Disulfide by Design” algorithm. The disulfide variant showed substantially improved thermostability with an eleven-fold increase in the t1/2 value at 60°C and a 7°C increase of Tm compared with the parent enzyme, probably contributed by the stabilization of the geometric structure of the lid region. The additional disulfide bond did not interfere with the catalytic rate (kcat) and the catalytic efficiency towards the short-chain fatty acid substrate, however, the catalytic efficiency of the disulfide variant towards pNPP decreased by 1.5-fold probably due to the block of the hydrophobic substrate channel by the disulfide bond. Furthermore, in the synthesis of fatty acid methyl esters, the maximum conversion rate by RCLCYS reached 95% which was 9% higher than that by RCL. This is the first report on improving the thermostability of the lipase from R. chinensis by introduction of a disulfide bond in the lid hinge region without compromising the catalytic rate.